Coenzyme Q10: Role in Less Common Age-Related Disorders - David Mantle; Iain P. Hargreaves (MDPI AG, 2022)
In this article we have reviewed the potential role of coenzyme Q10 (CoQ10) in the pathogenesis and treatment of a number of less common age-related disorders, for many of which effective therapies are not currently available. For most of these disorders, mitochondrial dysfunction, oxidative stress and inflammation have been implicated in the disease process, providing a rationale for the potential therapeutic use of CoQ10, because of its key roles in mitochondrial function, as an antioxidant, and as an anti-inflammatory agent. Disorders reviewed in the article include multi system atrophy, progressive supranuclear palsy, sporadic adult onset ataxia, and pulmonary fibrosis, together with late onset versions of Huntington's disease, Alexander disease, lupus, anti-phospholipid syndrome, lysosomal storage disorders, fibromyalgia, Machado-Joseph disease, acyl-CoA dehydrogenase deficiency, and Leber's optic neuropathy.